Na labuta do carvoejar: trabalho e modernização no setor carvoeiro no norte de Minas Gerais - Mendes, Joelena de Jesus (2018)
The production of charcoal is a prominent activity in the brazilian economy, mainly in the State of Minas Gerais, where its production has as main destination the steel industry. In Brazil, the activity of charcoal was marked by processes of hard and intense work and in many cases "analog to slave labor". In the last decade of the XX Century and the beginning of the XXI Century, the production of charcoal in Minas Gerais underwent a process of restructuring, this process changed so how to produce as the lives of those involved in the production. This research has as analyze the charcoal production process in the north of the State of Minas Gerais, considering the work process, the socioeconomic profile of the workers and the current context. The new production context contrasts with the traditional forms of charcoal production in a scenario of great social, economic and environmental impacts. This contrast takes place in the form of production and organization of work in charcoal and coal-mining companies, where, at the same time as they have real industries in this field, there are visible archaic productions, small manufactures that go back to forms of production considered as exceeded by this sector.The labor allows understand the capitalist society and its way of organize, because it has significant importance in social life, besides impacting individual workers.